Ashwagandha-Withania somnifera for Sustainable Socioeconomic Empowerment - Deore, Sharada Laxman; Baviskar, Bhushan Arun; Khadabadi, Somshekhar; Kide, Anjali Ashok; Vighne, Ram Chhatrapati (Pharmacognosy Reviews)
Ashwagandha, a renowned medicinal plant within the AYUSH (Ayurveda, Yoga, Unani, Siddha, Homeopathy) System, stands as a plant of paramount significance due to its multifaceted health benefits. Recognizing its pivotal role, the AYUSH Ministry, Delhi’s National Medicinal Plants Board (NMPB) launched the "Ashwagandha - A Health Promoter" campaign in the year 2022. This initiative signifies the plant's potential in promoting health and well-being. This comprehensive review endeavours to elucidate various facets of Ashwagandha, encompassing pharmacognosy, phytochemistry, conservation strategies, cultivation practices, therapeutic applications, market dynamics, exploration of value-added products and an overview of current research endeavours.
Keywords: Ashwagandha; Withania somnifera; Solanaceae; Value added products